EFEKTIVITAS PEMBERIAN KOMPRES LIDAH BUAYA (ALOE VERA) DAN KOMPRES AIR HANGAT TERHADAP PENURUNAN SUHU TUBUH BALITA PASCA IMUNISASI DPT-HB - Wahyuni Wahyuni; Rina Setia Agustin (Universitas Fort de Kock Bukittinggi, 2022)
Data from Tabir Lintas Community Health Center, immunization coverage of DPT-HB I/ Polio II is 98%, DPT-HB II/Polio III is 93%, DPT-Hb III/Polio IV is 94%, and advanced DPT-Hb immunization is 32%. 3 out of 10 babies have a high fever. The purpose of this study was to determine the effectiveness of giving aloe vera compresses and warm water compresses to decrease the body temperature of toddlers after DPT-HB immunization. The research design used was a quasiexperimental design with a two-group design, sample in this study was accidental sampling with a sample of 40 people, which was divided into 20 toddlers given aloe vera compress and 20 toddlers given warm water compresses, data collection with observation sheets with data analysis using the ttest. Based on the results obtained, the average decrease in body temperature of toddlers after being given an aloe vera compress was 0.64°C. Meanwhile, in warm water compresses, the average decrease in toddler body temperature after being given a water compress was 0.465 °C. The results of the Paired T-Test showed that there was an effect of aloe vera compress and warm water on the decrease in body temperature of toddlers after DPT-HB immunization. The results of the independent T-Test test with a p-value of 0.004 < α (0.05) means that there was a difference between an aloe vera compress and a warm water compress. Based on the results of the study, there was an effect of aloe vera compress and warm water on decreasing temperature, there was a difference between aloe vera compress and warm water compress with a mean different value of 0.25°C, meaning that aloe vera was more effective than warm water. It is hoped that mothers who have toddlers will use aloe vera as an alternative for handling fever in toddlers after DPT-HB immunization Keywords: DPT-HB, Aloe Vera, Warm Water Reference : 36 (2012-2021)